Metabolite profiling and antipathogenic properties of Rhizophora mucronata against marine leech Pterobdella arugamensis and Vibrio species in hybrid grouper - Fui, Jin Wong; Wei, Sheng Chong; Yoong, Soon Yong; Jen, Kit Tan; Rossita Shapawi; Muhammad Dawood Shah (Springer Science+Business Media, 2025)
Aquaculture is becoming a vital food source globally, but intensive fish farming often leads to disease outbreaks due to stress from high stocking density or environmental factors. One notable issue is the parasitism caused by the marine parasitic leech Pterobdella arugamensis. This parasite affects groupers and other marine cultured fish with symptoms of malnutrition, anorexia, and death. Additionally, wounds from the parasitism lead to secondary infections like vibriosis. As consumer demand for safe and sustainable seafood grows, interest in natural, plant-derived treatments has increased. This study explored the antiparasitic and anti- Vibrio potential of Rhizophora mucronata, a mangrove species that coastal communities use as traditional medicine. Methanol, chloroform, and hexane extracts of the plant were tested against P. arugamensis and five pathogenic Vibrio strains (V. alginolyticus, V. anguillarum, V. harveyi, V. parahaemolyticus, and V. owensii). The extracts were further analysed with mass spectrometry techniques, including GC–MS and LC-QTOF-MS, to identify important metabolites. All extracts exhibited 100% mortality to P. arugamensis with a dose-dependent activity. Methanol extract took the shortest mortality time, ranging from 15.48 ± 1.7 min to 95.03 ± 4.02 min at concentrations of 100 to 12.5 mg/ml, followed by chloroform and hexane extracts, with a mortality time of 25.76 ± 0.58 to 125 ± 2.56 min and 37.45 ± 1.21 to 128.92 ± 3.18 min, respectively. The anti-Vibrio assay revealed that the methanol extract resulted in the highest number of inhibitions against V. alginolyticus, V. anguillarum, and V. harveyi, while the chloroform and hexane extracts were effective only against V. harveyi. The GC–MS revealed six, eight, and seven metabolites in the methanol, chloroform, and hexane extracts, respectively, while the LC-QTOF-MS revealed 92 metabolites in the methanol extract, 37 metabolites in chloroform, and 43 metabolites in hexane extracts. The profiling screening revealed that the methanol extract is rich in flavonoids and phenolics, while the chloroform and hexane extracts mainly contained fatty acids and terpenoids. The identified metabolites that are known to fight parasites and bacteria, including benzothiazole, calendoflavoside, rutin, lupeol, oleanolic acid, and kaempferol, are found in the R. mucronata as well. The findings showed that R. mucronata, particularly its methanol extract, is a promising biocontrol agent against P. arugamensis and Vibrio infections in the aquaculture system.